Structural, optoelectronic and mechanical properties of PECVD Si-C-N films: An effect of substrate bias. (December 2018) - Kozak, A.O.; Ivashchenko, V.I.; Porada, O.K.; Ivashchenko, L.A.; Tomila, T.V.; Manjara, V.S.; Klishevych, G.V.
Abstract: Structural, optoelectronic and mechanical properties of amorphous silicon carbon nitride (Si-C-N) thin films produced by plasma enhanced chemical vapor deposition (PECVD) at different negative substrate biases (Ud ) are studied. The films are characterized by X-ray diffraction, atomic force microscopy, Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, optical transmittance spectroscopy, nanoindentation as well using the results of the measurements of photoluminescence (PL) and PL excitation (PLE) spectra. All deposited films are found to be X-ray amorphous. An increase in Ud leads to: a smoothing of the film surface; a decrease of the transparency; an increase of refractive index from 1.69 to 1.92; a decrease of the energy gap from 4.15 to 2.38 eV; an increase in nanohardness and elastic modulus from 14 GPa to 24 GPa and from 147 GPa to 190 GPa, respectively. These results were explained in terms of the bonding configuration from XPS and FTIR measurements. The PL spectra of the films deposited at lower negative substrate bias have one PL band in the region between 530 and 540 nm, whereas the PL spectra of the films deposited at higher negative substrate bias show two PL bands at 530–570 nm and 640–650 nm. On the basis of the PLE data, it was shown that these PL bands are related to the electronic recombination between the conduction band and the valence bands and their tails within the amorphous N-rich and C-rich Si-C-N-O-H networks.